Effect of Fall-Applied Residual Herbicides on Rice Growth and Yield. (20th August 2018) - Lawrence, Benjamin H.; Bond, Jason A.; Edwards, Henry M.; Golden, Bobby R.; Montgomery, Garret B.; Eubank, Thomas W.; Walker, Timothy W.
Abstract: Glyphosate-resistant (GR) Italian ryegrass is one of the most troublesome weeds in Mississippi row crop production. Fall-applied residual herbicide applications are recommended for control of GR Italian ryegrass. However, carryover of residual herbicides applied in fields for rice production can have a negative impact on rice performance. Field studies were conducted in Stoneville, MS, to determine the effects of fall-applied residual herbicides on rice growth and yield. Herbicide treatments included suggested use rates (1×) of clomazone at 840 g ai ha –1, pyroxasulfone 170 g ai ha –1, S -metolachlor 1, 420 g ai ha –1, and trifluralin 1, 680 g ai ha –1, and two times (2×) the suggested use rates in the fall before rice seeding. Pooled across application rate, pyroxasulfone, S -metolachlor, and trifluralin injured rice to an extent 28% to 36% greater than clomazone 14 d after emergence (DAE). Rice seedling density and height 14 DAE and rice maturity were negatively affected by all fall-applied herbicides except clomazone. Applications at 2× rates reduced rough rice yields in plots treated with pyroxasulfone, S -metolachlor, and trifluralin compared with clomazone. Pyroxasulfone applied at the 2× rate reduced rough rice yield 22% compared with the 1× rate. Rough rice yield was 90% or greater of the nontreated control in plots treated with either rate of S -metolachlor, and these were comparable with rough rice yields from plots treated with both rates of trifluralin and the 1× rate of pyroxasulfone. Early-season injury and reductions in seedling density and height 14 DAE, would preclude even 1× applications of pyroxasulfone, S -metolachlor, and trifluralin from being viable options for residual herbicide treatments targeting GR Italian ryegrass in the fall before rice seeding. Of the herbicides evaluated, only clomazone should be utilized as a fall-applied residual herbicide treatment targeting GR Italian ryegrass before seeding rice.